2015
DOI: 10.1111/1753-0407.12253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characteristics of maturity‐onset diabetes of the young compared with early onset type 2 diabetes in China

Abstract: Herein we report on 14 Chinese families with MODYX and describe its phenotype. Compared with early onset T2D, MODYX is characterized by lower BMI and decreased insulin-secreting capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…In the present study, 24/42 (57%) clinically suspected MODY cases had mutations identified. In contrast, a study from China suggested that MODY‐X (mutation of MODY genes was absent) accounted for the majority of clinical MODY cases in China . Our results are markedly different from previous findings in adult Chinese patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, 24/42 (57%) clinically suspected MODY cases had mutations identified. In contrast, a study from China suggested that MODY‐X (mutation of MODY genes was absent) accounted for the majority of clinical MODY cases in China . Our results are markedly different from previous findings in adult Chinese patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Families with MODY2 account for 1% of 146 unrelated Chinese families with MODY [5]. Zhang et al studied 14 Chinese families with MODY and did not find any GCK mutation or the other 12 known MODY genes [6]. Patients with MODY2 are usually asymptomatic, and diabetes is not always present in their family history.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MODY2 accounts for only 1% of Chinese MODY patients [5]. Recently, Zhang et al studied 14 Chinese MODY probands from unrelated families and 59 patients (age at onset ≤ 35 years) diagnosed as early onset T2DM, as well as nucleotide variations in promoters, exons and exon-intron boundaries of 13 known MODY genes by sequencing, and they did not find any GCK mutation or the other 12 known MODY genes [6]. Interestingly, we found three Chinese families with MODY2 over a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, MODY2 and MODY3 mutations constitute approximately 70% of MODY cases [ 12 ], while the other four types of MODY are more rarely found. For Asians, however, only 7.5%–10.3% of patients have mutations in MODY2 and MODY3 [ 13 ], and MODY with unknown cause (MODYX) accounts for 80–90% of clinical MODY cases [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, few reports concerning MODY gene mutations in Han Chinese families; thus additional mutational profiling is needed [ 13 , 14 ]. In this study, we screened 6 MODY genes ( HNF4A , GCK , HNF1A , IPF1 , HNF1B , and NEUROD1 ) for mutations in a Han Chinese family with suspected early-onset maternally inherited type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%